2023
DOI: 10.1371/journal.pone.0280791
|View full text |Cite
|
Sign up to set email alerts
|

How mindfulness, self-compassion, and experiential avoidance are related to perceived stress in a sample of university students

Abstract: University students constitute a population that is highly vulnerable to developing mental health problems, such as distress. The role of different variables associated with the development of states of stress has been studied in order to identify potential risk and protective factors. This study explored whether mindfulness, self-compassion, and experiential avoidance, while controlling for specific sociodemographic and academic variables, were potential significant protective or risk factors explaining perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
0
1
0
1
Order By: Relevance
“…As a result of all of this, interventions that aim to improve mental health in university students have been widely used ( Regehr et al, 2013 ). Specifically, it has been proposed that programmes aimed at reducing stress and improving well-being among university students should include experiential avoidance, self-compassion and mindfulness skills as therapeutic targets ( Martinez-Rubio et al, 2023 ). In fact, some interventions based on acceptance, compassion and mindfulness training have shown positive results in reducing psychological distress symptoms ( de Vibe et al, 2018 ; Patel et al, 2018 ; Dawson et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of all of this, interventions that aim to improve mental health in university students have been widely used ( Regehr et al, 2013 ). Specifically, it has been proposed that programmes aimed at reducing stress and improving well-being among university students should include experiential avoidance, self-compassion and mindfulness skills as therapeutic targets ( Martinez-Rubio et al, 2023 ). In fact, some interventions based on acceptance, compassion and mindfulness training have shown positive results in reducing psychological distress symptoms ( de Vibe et al, 2018 ; Patel et al, 2018 ; Dawson et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several scholars have argued that the measurement of SC through the SCS should consider the positive (SC) and negative (self-criticism) aspects as distinct and separate constructs, rather than treating them as a singular entity. 1,54,55 In a notable demonstration, an extensive meta-analysis incorporating eighteen distinct analyses revealed that the negatively rated items within the SCS exhibited a more robust association with psychopathology in comparison to the positive items. Consequently, this prompted the researchers to propose that the utilization of an overall scale score may exaggerate the connections between SC and negative affective disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Estudantes universitários constituem uma população altamente vulnerável ao desenvolvimento de problemas de saúde mental, sendo a Síndrome de Burnout um deles (Martínez-Rubio et al, 2023). A Síndrome de Burnout tem sido considerada um problema social de crescente importância entre pesquisadores e comunidade prática nos mais diferentes países.…”
Section: Introductionunclassified